Answering the call for values-based anti-doping education—An evidence-informed intervention for elite adolescent athletes in Germany and Austria - Manges, T.; Seidel, K.; Walter, N.; Schüler, T.; Elbe, A.-M. (Frontiers in Sports and Active Living, 2022)
Doping has serious negative consequences for athletes and the integrity of sports, implying the need for effective prevention programs. Since educating young athletes about doping-related knowledge is deemed to be not sufficiently effective to minimize doping, a focus on values, emotions and morality is seen as a promising approach and previous research indicates which variables exactly could be addressed in anti-doping efforts. These variables are anticipated guilt, empathy, moral disengagement, and collective moral norms, since these constructs have been strongly and consistently linked to doping intention, likelihood, or behavior. Therefore, the purpose of this study was to develop a values-based anti-doping intervention, which targets the aforementioned variables, and to evaluate its effectiveness in producing changes in outcomes in comparison to an information-based intervention and a waiting control group. To evaluate their effectiveness, both interventions, which each consist of six 45-min sessions (one session per week) were implemented in a sample of 321 young elite athletes, aged 13-19 years, from a broad range of team and individual sports. Thirty different teams, training groups or classes were randomly assigned to either the values-based intervention, the information-based intervention, or to a waiting control group. Doping intention, doping susceptibility as well as the above mentioned variables were assessed at pre- and posttest and, for participants of the values- and information-based conditions also at a 3 to 4-month follow up. Within a multilevel modeling framework general linear mixed regression analyses revealed that the values-based intervention, compared to the control group, was able to decrease athletes' moral disengagement and increase their anticipated guilt immediately after the intervention (at posttest), whereas no effects for the information-based intervention emerged. Looking at how the outcomes developed over time (i.e., at the follow up measurement), it could be demonstrated that the reduction in moral disengagement sustained. The increase in anticipated guilt, however, was not sustainable and, surprisingly, decreased from post to follow up. Furthermore, athletes in the values-based intervention reported higher empathy from post to follow up, which could possibly indicate a "delayed" effect. This study provides support that a values-based approach can produce changes in some, yet, not all addressed variables and specific elements from this intervention could potentially be a useful addition to traditional anti-doping education (i.e., information provision).